Regulation of the α-Galactosidase Activity in Streptococcus pneumoniae: Characterization of the Raffinose Utilization System - Rosenow, Carsten; Maniar, Mita; Trias, Joaquim

(untitled) (Genome Research, 1999)
A 10.2-kb gene region was identified in the Streptococcus pneumoniae genome sequence that contains eight genes involved in regulation and metabolism of raffinose. The genes rafR andrafS are transcribed as one operon, and their gene products regulate the raffinose-dependent stimulation of a divergently transcribed second promoter (PA ) directing the expression of aga, the structural gene for α-galactosidase. Raffinose-mediated transcription from PA results in a 500-fold increase in α-galactosidase activity in the cell. A third promoter within the cluster is responsible for the transcription of the remaining five genes (rafE, rafF, rafG,gtfA, and rafX), whose gene products might be involved in transport and metabolism of raffinose. The presence of additional internal promoters cannot be excluded. The agapromoter PA is negatively regulated by the presence of sucrose in the growth medium. Consistent with catabolite repression (CR), a DNA sequence with high homology to the CRE (cis-active element) was identified upstream of the aga promoter. Sucrose-mediated CR depends on the phosphoenolpyruvate: sucrose phosphotransferase system (PTS) but is unaffected by a mutation in a gene encoding a homolog of the CRE regulatory protein CcpA.